2018
DOI: 10.3390/ijgi7120489
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Dispersion Modelling Using Spatial Analyses

Abstract: Air pollution dispersion modelling via spatial analyses (Land Use Regression—LUR) is an alternative approach to the standard air pollution dispersion modelling techniques in air quality assessment. Its advantages are mainly a much simpler mathematical apparatus, quicker and simpler calculations and a possibility to incorporate more factors affecting pollutant’s concentration than standard dispersion models. The goal of the study was to model the PM10 particles dispersion via spatial analyses in the Czech–Polis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Observed PM 10 concentrations vs. Gaussian model results.Both linear regression-based LUR models provided a similar performance, the R 2 of the models was 0.639 for the emission factor linear model and 0.652 for the linear model based on the Gaussian model results. The results of these LUR models are similar to those of the other LUR models, which are 0.65 in Bitta et al[31], 0.58 in Liu et al[49] or 0.66-0.76 in Masiol et al[50]. A more detail comparison of these studies and the model of the study is not possible, since each model used a different set of variables, different time scales, etc.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Observed PM 10 concentrations vs. Gaussian model results.Both linear regression-based LUR models provided a similar performance, the R 2 of the models was 0.639 for the emission factor linear model and 0.652 for the linear model based on the Gaussian model results. The results of these LUR models are similar to those of the other LUR models, which are 0.65 in Bitta et al[31], 0.58 in Liu et al[49] or 0.66-0.76 in Masiol et al[50]. A more detail comparison of these studies and the model of the study is not possible, since each model used a different set of variables, different time scales, etc.…”
supporting
confidence: 67%
“…Factors of land cover and factors representing emission were calculated in a similar manner. Based on the experience from Bitta et al [31], all factors representing land cover and emission were enumerated as weighted averages, where the weights were defined by the estimated probability of the wind direction.…”
Section: Input Factors Of the Land Use Regressionmentioning
confidence: 99%
“…The model situation describes a case when there was a chemical substance leakage into the environment in a given space with the dimensions of 40 × 40 km [21]. It is considered to be such a toxic substance that it requires individual protection before the process of decontamination begins.…”
Section: Application Of Multi-criterial Analysis For Solution Of a Comentioning
confidence: 99%
“…Weather conditions, combined with a high industrialization of regions lying along the border of Czech Republic and Poland, influence the formation of long smog episodes with PM10 concentrations in the atmosphere at the value of several hundred micrograms in a cubic meter (Moravian-Silesian Region, 2019). However, it has been observed that the main source of dust pollution in the area of the Polish-Czech border between most populated areas of Ostrava and Katowice (Silesian Province) is the residential heating fired with solid fuels [Bitta et al, 2018], participating at the level of not less than 21% in overall air contamination with dusts. It particularly concerns PM10, which is one of the major air pollutants produced by the combustion of solid fuels, such as biomass and coal [Chafe et al, 2015].…”
Section: Introductionmentioning
confidence: 99%